STORM WAVE MODELING AND IT’S VALIDATION BY THE MODERN WAVE MEASUREMENT DEVICES - Hung, Nguyen Manh; Dien, Duong Cong (Vietnam Journal of Marine Science and Technology, 2008)
The storm wave is a marine hydro dynamical parameter which is very serious, especially for the marine constructions which often withstand all the severe weathers in the sea. The East Sea is suffered from one of five storm generation regions in the world that explain why the storm wave modeling is an important task of the researchers. in the paper, the storm wave modeling has been presented. The main focus has been paid in the calibration and verification procedure using the modern types of wave measurement, among them the satellite wave measurements are the most optimistic. The results of validation show that the storm wave modeling is sufficient for the marine construction design and activities.